ChemInform Abstract: Ruthenium‐Catalyzed Direct C‐3 Oxidative Olefination of Imidazo[1, 2‐a]pyridines. Issue 8 (February 2015) - Zhan, Haiying; Zhao, Limin; Li, Naiying; Chen, Longbin; Liu, Jingyun; Liao, Jinqiang; Cao, Hua
Abstract Excellent E‐stereoselectivity is obtained in the reaction with acrylates as olefination reagent, whereas the reaction of acrylonitrile gives a mixture of E/Z‐isomers.